Skin maculae, chronic diarrhea, cachexia, and splenomegaly-Late presentation of the first autochthonous case of visceral leishmaniasis in Tanzania. - Oliver Henke; Priscus John Mapendo; Alex Mremi; Lilian Gasper Mmbaga; Angela Elisha Pallangyo; Thomas Harbaum; Elifuraha Mkwizu (PLoS Neglected Tropical Diseases)
A 20-year-old man from Simanjiro district in northern Tanzania presented with a 3-year history of splenomegaly, fatigue, cachexia, skin maculae, and recent onset of watery diarrhea at Kilimanjaro Christian Medical Centre (KCMC) in Northern Tanzania. Due to laboratory findings of pancytopenia, diagnostic workup included bone marrow aspiration cytology and biopsy. Although the rapid test (IT LEISH, rK39 RDT) was negative, blood smear showed amastigote forms of leishmaniasis in macrophages. Repeat bone marrow aspiration and PCR eventually confirmed visceral leishmaniasis (VL). The patient denied travel to known endemic areas of VL. Treatment was initiated with Amphotericin B, but the patient died on the fourth day of treatment from respiratory insufficiency. An autopsy revealed massive organ manifestations of VL. This is the first reported autochthonous case of VL in Tanzania. Clark and colleagues detected the vector Phlebotomus martini in Northern Tanzania in 2013, in a region bordering the district of our patient. The negative rapid test draws attention to the fact that sensitivity and specificity were found to be low in East African VL patients as displayed earlier by a Kenyan study. Therefore, tissue samples (spleen or bone marrow) remain necessary for diagnosis. The variety of symptoms in this presented case was remarkable, including the occurrence of post-kala-azar dermal leishmaniasis (PKDL) and VL at the same time. This has been described in East African VL cases before as well as the occurrence of chronic diarrhea. An elongated undiagnosed period likely led to a mixed clinical picture that included hepato-splenomegaly, PKDL, cachexia, and diarrhea.